2013
DOI: 10.1049/iet-ifs.2012.0192
|View full text |Cite
|
Sign up to set email alerts
|

Antivirus performance characterisation: system‐wide view

Abstract: Cyber security threats are still big concerns of the cyber world. Even though many defense techniques have been proposed and used so far, the antivirus (AV) software is very widely used and recommended for the end-users-PC community. Most effective AV products are commercial and thus competitive and it is not obvious for security researchers or system developers how exactly the AV works or how it affects the whole system. The AV adds layers of complications over the already layered, complicated systems. Becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Al-Saleh et al [84] analyze the intrusiveness of two AV solutions (Symantec and Sophos) using a Windows event logger in an attempt to evaluate the impact on system performance. Their results show that the presence of an AV engine noticeably impacts on regular program execution, not only in terms of CPU usage, but also in IO operations and paging issues.…”
Section: Av Performance and Alternativesmentioning
confidence: 99%
“…Al-Saleh et al [84] analyze the intrusiveness of two AV solutions (Symantec and Sophos) using a Windows event logger in an attempt to evaluate the impact on system performance. Their results show that the presence of an AV engine noticeably impacts on regular program execution, not only in terms of CPU usage, but also in IO operations and paging issues.…”
Section: Av Performance and Alternativesmentioning
confidence: 99%
“…Furthermore, AV performance is analyzed in [8], where the authors quantify how devices' performance is affected by AV execution, and [9], a characterization and evaluation of AV overhead. In addition, the authors in [10] compare the design of 30 top AV solutions focusing on their detection and prevention capabilities.…”
Section: Previous Workmentioning
confidence: 99%
“…Ramilli et al (2011) showed that the detection of Avs can be avoided by splitting it into parts that are distributed over several processes. Finally, performance studies on AVs to find their bottlenecks or improve scanning times have also been conducted (Vasiliadis and Ioannidis, 2010;Miretskiy et al, 2004;Lin et al, 2011;Al-Saleh et al, 2013).…”
Section: Related Workmentioning
confidence: 99%